Investigation on underutilized plants used as daily medication, fruit source and traditional ceremonies in Bireuen regency, Aceh, Indonesia - Ernawita; Nuraida; Fauziah, Ida; Satriawan, Halus (Plant Science Today, 2024)
Bireuen is a regency that constitutes 3.13 % of the total area of the Aceh province, with elevations ranging from 0 to 2637 m above sea level (asl). Although the biodiversity of this regency is expected to be high, there is limited data available on its plant species. Many of the plants are believed to be considered underutilized. Therefore, this study aimed to investigate some ethnobotanical aspects of underutilized plant species in Bireuen Regency, Aceh. The study was carried out as a survey using an open questionnaire in 17 districts, with 70 respondents selected through purposive sampling. Quantitative indices such as Relative Frequency of Citation (RFC), Use Value (UV), Informant Consensus Factor (ICF) and Pearson Correlation were performed on RFC and UV to determine the relationship between the 2 indices. A total of 40 families and 74 plant species were recorded, identified and grouped based on their use as traditional medicine (32 families and 47 species), fruit consumption (12 families and 21 species) and traditional ceremonies (15 families and 17 species). The common methods used to prepare medicine based on these local plants were crushing or boiling to treat mild symptoms and diseases. The fruit of these plants was often consumed and some plant information is scarcely available, such as buah brahim (Uvaria siamensis) and kayee kunyet (Polyalthia littoralis). The ICF value showed that the category with the highest consensus factor was traditional ceremonies (0.85), followed by consumption as fruit (0.84), and traditional medicine (0.68). This study revealed that many local plants commonly used as part of local culture had potential medicinal properties. Therefore, further investigations are recommended to validate the use of indigenous plants and preserve the knowledge.